Antenatal iron deficiency in an urban Malaysian population - Zaleha Abdullah Mahdy; Jumaida AB; Muhammad Za’im Sh; Rahana Abd Rahman; Mukudan K; Zaleha Md Isa (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Iron deficiency anemia is the most common form of anemia in pregnancy. The present study was carried out to determine the prevalence of antenatal anemia and iron deficiency in the Malaysian population and its correlation with socio-demographic and obstetric profile. It was a cross-sectional study conducted at an urban health clinic over a period of six months. A single blood sample was drawn from apparently healthy pregnant mothers at antenatal booking and sent for laboratory assessment of full blood count and serum ferritin as screening tools for anemia and iron status. SPSS version 19.0 was used for statistical analyses. The results showed that out of 250 subjects, 43.6% had anemia and 31.6% had iron deficiency. Whilst 47.7% of subjects with anemia were iron deficient, 19.1% of subjects without anemia were also iron deficient. Serum ferritin correlated negatively with period of gestation at booking (p<0.001), with 77.6% of these women not having prior iron supplements. Serum ferritin was also significantly lower among grandmultiparae (p=0.01). Iron deficiency was significantly (p=0.024) more common among Indians (42.5%) compared to Malays (33.5%) and Chinese (13.0%). In conclusion, continuation of the current practice of routine antenatal iron supplementation is still warranted and justifiable in Malaysia as there is high prevalence of iron deficiency in pregnancy not only in the presence of anemia but also in the presence of normal hemoglobin values.